Osteopontin expression in vitreous and proliferative retinal membranes of patients with proliferative vitreous retinopathy - Liu, Xiao-Yi (International Journal of Ophthalmology Press, 2011)
AIM: To analyze osteopontin (OPN) expression in vitreous and proliferative retinal membranes of patients with proliferative vitreous retinopathy (PVR). METHODS: A total of 54 vitreous fluid samples were obtained between 2009 and 2010, which contained 45 with PVR (group A) and 9 without PVR (group B). Enzyme-linked immunosorbent assay was applied to quantify the OPN concentrations in vitreous fluid. Four samples of proliferative retinal membrane were also obtained at the time of vitrectomy, and their contents of OPN were measured by Real-time RT-PCR. RESULTS: The OPN levels in the vitreous fluid were 778.48±62.06ng/mL in group A and 452.99±32.52ng/mL in group B. The vitreous OPN levels in group A were significantly higher than those in group B and to rise by time in the early stages of PVR. The average OPN levels in the proliferative retinal membranes (F=0.14) were also higher than those in the retinal pigment cells (F=0) using Real-time RT-PCR. CONCLUSION: The high vitreous and proliferative retinal membrane OPN levels in PVR suggest that OPN might promote the development of PVR. The vitreous OPN concentrations are rising by the time in the early phases of PVR.